Particulate Matter Exposure and Cardiopulmonary Differences in the Multi-Ethnic Study of Atherosclerosis - Aaron, Carrie P. (Environ Health Perspect, 2016)
BACKGROUND: Particulate matter (PM) exposure may directly affect the pulmonary vasculature. Although the pulmonary vasculature is not easily measurable, differential associations for right ventricular (RV) and left ventricular (LV) mass may provide an indirect assessment of pulmonary vascular damage. OBJECTIVES: We tested whether long-term exposure to PM < 2.5 μm (PM2.5) is associated with greater RV mass and RV mass/end-diastolic volume ratio relative to the LV. METHODS: The Multi-Ethnic Study of Atherosclerosis performed cardiac magnetic resonance (CMR) imaging among participants 45–84 years old without clinical cardiovascular disease in 2000–2002 in six U.S. cities. A fine-scale spatiotemporal model estimated ambient PM2.5 exposure in the year before CMR; individually weighted estimates accounted for indoor exposure to ambient PM2.5. Linear regression models were adjusted for demographics, anthropometrics, smoking status, cardiac risk factors, and LV parameters, with additional adjustment for city. RESULTS: The 4,041 included participants had a mean age of 61.5 years, and 47% were never smokers. The mean ambient PM2.5 was 16.4 μg/m3 and individually weighted PM2.5 was 11.0 μg/m3. PM2.5 exposure was associated with greater RV mass [ambient: 0.11 g per 5 μg/m3 (95% CI: –0.05, 0.27); individually weighted: 0.20 g per 5 μg/m3 (95% CI: 0.04, 0.36)] and a greater RV mass/end-diastolic volume ratio conditional on LV parameters. City-adjusted results for RV mass were of greater magnitude and were statistically significant for both measures of PM2.5, whereas those for RV mass/end-diastolic volume ratio were attenuated. CONCLUSIONS: Long-term PM2.5 exposures were associated with greater RV mass and RV mass/end-diastolic volume ratio conditional on the LV; however, additional adjustment for city attenuated the RV mass/end-diastolic volume findings. These findings suggest that PM2.5 exposure may be associated with subclinical cardiopulmonary differences in this general population sample. CITATION: Aaron CP, Chervona Y, Kawut SM, Diez Roux AV, Shen M, Bluemke DA, Van Hee VC, Kaufman JD, Barr RG. 2016. Particulate matter exposure and cardiopulmonary differences in the Multi-Ethnic Study of Atherosclerosis. Environ Health Perspect 124:1166–1173; http://dx.doi.org/10.1289/ehp.1409451